Researching intimate partner violence against women (IPVAW): overcoming gender blindness by improving methodology in compliance with measurement standards - Sánchez-Prada, Andrés (Journal of family violence, 2023)
Intimate Partner Violence Against Women (IPVAW) has been defined as a violation of human rights and a serious public health problem rooted in social inequality between women and men. Nevertheless, a significant amount of scientific literature on the topic of IPVAW continues to exclude the gender perspective in both research design and the interpretation of results, despite its conceptual and explanatory relevance. This paper considers certain gender-blind practices in the research on IPVAW. Based on this analysis, we propose explicitly stating the theoretical assumptions inherent in the definition of the construct and clarifying the intended interpretation for measures, so that they can be incorporated into the analysis of validity, and we argue in favor of the need for interdisciplinary studies based on multicausal explanatory models, which incorporate the category gender as a transversal explanatory factor of this type of violence, as well as multi-method approaches, with the aim of overcoming issues of construct underrepresentation and construct-irrelevant variance.